Food security and climate actions in Ethiopia: A possible way forward - Mulatu, Kalkidan; Chemarin, Charlotte (2026)
The Ethiopia FABLE team and the FABLE Secretariat collaboratively developed an ambitious illustrative national food and land use pathway for Ethiopia based on national commitments and aligned with the FAO Global Roadmap framework.